(untitled) (One Health Journal of Nepal, 2023)
Introduction: Menstruation is a natural physiological process that starts in females usually between the ages of 11 and 15 (menarche) and ends at menopause. Menstrual hygiene, one of the crucial components for the well- being of women, has significant implications for girls’ education, empowerment, and overall social development. But yet the topic remains shrouded in taboo and misconceptions. This study focuses on the knowledge, attitudes, and practices of school-going adolescents regarding menstrual hygiene in Tokha Municipality, Kathmandu. Methods: A descriptive cross-sectional study involved 335 students in grades 8, 9, and 10 from public schools in Tokha Municipality, Kathmandu. Students were selected through random sampling, with prior ethical approval. Adolescent girls who hadn’t experienced menarche were excluded. The research utilized UNICEF’s Menstrual Hygiene Management (MHM) assessment tool and conducted data analysis using SPSS version 20. Results: Out of total adolescents, more than eight out of ten males (86%) were aware that menstruation is a normal physiological process whereas the majority of females (94.5%) were aware of the same fact. The percentage of female adolescents facing restriction during menstruation was 34.7% and the percentage of adolescents having an average level of attitude towards menstruation was 60.3%. The majority of female adolescents participating in the study had above-average levels of practice on menstruation. Conclusions: The study findings indicate a prevalent awareness of menstruation as a natural process among adolescents in Tokha Municipality, Kathmandu. However, challenges such as restrictions during menstruation and average attitudes suggest the need for targeted interventions to foster a more supportive environment for adolescent well-being.